What's Positive in a Pandemic? Journalism Professionals' Perspectives on Constructive Approaches to COVID-19 News Reporting. (12th March 2022) - van Antwerpen, Natasha; Turnbull, Deborah; Searston, Rachel A.
ABSTRACT : Throughout COVID-19, the proliferation of misinformation and the impact of negative news on mental health highlights a tension between news media as a source of essential public health information and news as a source of distress. A suggested approach to reporting which remains informative while tempering audience distress is constructive journalism. We investigated the benefits and applications of constructive news reporting during COVID-19 from the perspectives of journalism professionals interested in constructive approaches. Eleven participants from four continents were interviewed in the first two months of the pandemic. The data were analysed using thematic analysis, and two themes produced: "Sober not sensational" and "What's positive in a pandemic?" Six subthemes were also produced: "beyond the numbers", "slower reporting", "understanding uncertainty", "solutions", "we're all in the same boat" and "awakening". Constructive approaches were seen to help journalists navigate their roles as educators and to provide hope without inciting undue panic. Our interviews suggest constructive news reporting could assist in balancing informativeness and public mental health throughout the pandemic. More work is needed, however, that incorporates randomised controlled testing to establish whether constructive journalism techniques meaningfully impact audience mental health beyond standard approaches.